Portrait of psychological condition people in Banda Aceh and Aceh Besar after ten years of earthquake and tsunami - Nursan Junita; Eka Rumaisha; Yulia Direzkia (Universitas Muhammadiyah Malang, 2015)
The aim of this study was obtained a portrait of Psychological condition of people in Banda Aceh & Aceh Besar After ten years of Earthquake and Tsunami Disaster. The traumatic event of December 26th, 2004, seriously impacts of psychological aspect of human being in Aceh. Moreover, people who experienced the disaster will predict to have seriously psychological problem in their life which is called PTSD (Post Traumatic Stress Disorder). Therefore, the study would like to see how the psychological condition of people in Banda Aceh, recently after ten years of earthquake and tsunami disaster through mental health aspect. The method was applied in this study was the qualitativeapproach that used the technique of Focus Group Discussion (FGD) by collecting the data from three (3) group of society. The subject were from kota Banda Aceh that representative of three (3) zone area that affected by earthquake and tsunami. The criteria of this zone were; Zone (1) is the most severe exposure to tsunami (within 0-3 km of the coastline); Zone (2) is a moderate impairment area that exposed to tsunami (within 3-5 km of coastline); Zone (3) is the area not exposed to tsunami (within 5-7 km of coastline). The result of study showed that people in zone 1 and zone 2, still have psychological reaction of trauma symptom such as numbing when re-experiencing the earthquake, easily worried, anxious, panic, and have sleep disturbance. However, the symptom does not disturbing their daily activities of life, so they are productive. Their coping skill also improves in facing the problem as well as more religious, acceptance, resilience, stronger, patience and more alert of disaster preparedness. However, the people in zone 3 does not show the psychological symptom of trauma, but they also become aware as well as take it this as the lesson learn for them this experienced.Key words: psychological of trauma, PTSD, tsunami Aceh, resilience